External Pin Fixation with Early Flap Coverage for Open Tibial Fractures with Soft Tissue Loss (Journal of Medicine, 2010)
Meaningful data on the management of open tibial fractures cannot be obtained unless one categorizes the injury according to fracture type, degree of soft tissue loss and the velocity of the injury. Treatment by converting the type III injury to a type II injury with well vascularized soft tissue is presented. Eighteen patient with 20 type III and type III(a) wounds were treated in a prospective fashion employing a combined orthopedic and plastic surgical scheme based on the tenets of early radical debridement, a "second look" operation, muscle or fasciocataneus flap cover within the first 3 weeks for injury. All fractures united in a mean time of 6.0 months. The mean hospitalization was 6.2 weeks. There have been chronic infection, osteomyelitis nonunion, shortening or tissue breakdown. Keyword: Open tibial fractures, external pin fixation DOI:10.3329/jom.v11i1.4265 J Medicine 2010: 11: 28-32